Identifying nesting grounds for juvenile migratory birds with dual isotope: an initial test using North American raptors - Brooke E. Crowley; Clément P. Bataille; Bruce A. Haak; Kaitlin M. Sommer (Ecosphere, 2021)
Abstract Understanding seasonal mobility, population connectivity, and site fidelity is critical for managing and preserving migratory species. We investigated the potential of coupling strontium (87Sr/86Sr) and hydrogen (δ2H) isotopes in feathers for quantitatively constraining natal origin for juvenile migratory predatory birds (raptors) using a probabilistic framework. We first calibrated single‐isotope models that predict spatial isotope variability in raptor feathers (called isoscapes) by analyzing and compiling isotope data for juvenile birds with known origins in North America and comparing their values to existing isotopic baselines in precipitation (for δ2H) and bioavailable strontium (for 87Sr/86Sr). We then compared the potential of hydrogen and strontium isotopes for refining geographic assignments either independently or combined. While yielding very different probability maps, hydrogen and strontium isotopes performed equally well at constraining regions of natal origin. However, thanks to the complementarity of these isotopes, dual δ2H and 87Sr/86Sr assignments increased predictive precision by an order of magnitude compared to either isotope alone. Lastly, we used the models to predict natal origin for juveniles with unknown origins that were sampled in southwestern Idaho, USA, during their autumn migration. The precision of geographic assignments for birds with unknown origins varied. Nevertheless, dual‐isotope assignments clearly distinguished individuals born outside of southwestern Idaho, and overall, predicted geographic assignments matched breeding ranges for the study species. Quantitative dual‐isotope geographic assignments enhance our ability to predict natal range of migratory raptors and complement other methods for monitoring movement and population connectivity. Combining isotopic data from feathers with other intrinsic geochemical and genetic data, as well as extrinsic markers, such as transmitters or bands, and niche‐modeling approaches will further refine key nesting areas for migratory birds.